Consequences of Enterprise Social Media Network Positions for Employees - Sebastian Schötteler; Sven Laumer; Heidi Schuhbauer (Business & Information Systems Engineering, 2023)
Employees often use enterprise social media (ESM) for communication, collaboration, and knowledge sharing, leading to ESM networks–that is, social networks of interrelated employees based on ESM. Many organizations possess ESM networks, and there is increasing research on their consequences for employees depending on how these employees are positioned in such networks. ESM network research is complex and consists of various interrelated dimensions. However, a synthesis of the abovementioned studies is lacking. Therefore, the current body of knowledge may obfuscate how the different dimensions interrelate, impeding a more holistic understanding of the consequences that employees may experience depending on their network positions. Moreover, there is little understanding of which research topics in this area have been addressed to date and where further research is needed. This paper addresses these gaps by means of a literature review and research agenda that synthesizes past studies. The results emphasize that whether ESM are beneficial for and exert a positive influence on employees largely depends on the employees' positions in the underlying networks.
Keywords: 000; Social network research; Enterprise social media; Enterprise social media networks; Enterprise social media network positions; Employee consequences